PRODUKTIVITAS, INVESTASI SUMBERDAYA MANUSIA, INVESTASI FISIK, KESEMPATAN KERJA TERHADAP KEMISKINAN DAN PERTUMBUHAN EKONOMI DI INDONESIA - Aimon, Hasdi (Program Studi Magister Ilmu Ekonomi, 2012)
ABSTRACT This study is focused on productivity, human resources investment, phisical investment and employment to proverty and economic growth in Indonesia. The proverty is influenced by education investment, health investment, productivity and economic growth. On the other hand, the economic growth part is affected by productivity, phisical investment, employment and proverty. From econometric study, we found that proverty and economic growth give causality and contribute significantly. The data series was taken from 1980-2009. Simultaneous model 2SLS is used to analyze education investment, health investment, productivity, phisical investment, employment, proverty and economic growth coefficients size. Before future analysis, we also checked stationary test, co-integration test and causalities between proverty and economic growth. We conclude that the government need to increase incentive in public sector and riel sector in order to increase investment and economic. Therefore, it can decrease proverty rate and increase economic growth in Indonesia. Keyword: Human resources investment, Phisical investment, Productivity, Proverty and Economic growth.